Strategic Communication in Political Crisis: The Case of Guillermo Lasso (2023) - Chavero, Palmira (2023)
The increase in the use of digital platforms and social networks by various actors in the public sphere has become one of the most significant areas of study in Communication studies in recent decades. Its utilization during political crises underscores the importance of strategic communication for political actors, as it transforms into crisis communication. In this work, we conduct an analysis of the digital strategic communication employed by the former president of Ecuador, Guillermo Lasso, during the political crisis caused by the impeachment trial against him in May 2023 and his subsequent call for early elections. To achieve this, we perform a critical analysis of the discourse presented in the tweets by the former president between May and July 2023. The results reveal a shift in his digital communication strategy and his relationships with other political actors following the announcement of early elections.